Development of experiment-based worksheet to improve critical thinking in human respiration - Biworo Frida Gurning; Fauziyah Harahap; Yusnadi Yusnadi (Inovasi Kurikulum, 2025)
Limited student engagement and underdeveloped critical thinking skills in elementary science learning prompted the development of an experiment-based student worksheet on the topic of the human respiratory system. This study aimed to produce a valid, practical, and effective instructional tool for fifth-grade learners. The development process employed a modified ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. Validation involved subject matter experts, media specialists, and language experts. Implementation engaged classroom teachers and students in assessing the practicality and effectiveness of the worksheet. Findings revealed that the worksheet content aligned with learning objectives, the visual presentation was appealing, and the language was clear and appropriate for elementary students. The evaluation process indicated that the product supported a more contextual and participative learning environment. Feedback from both teachers and students affirmed the worksheet's role in promoting critical thinking skills through well-structured experimental tasks. The overall quality of the worksheet demonstrated its potential as a relevant and meaningful learning medium that aligns with the principles of the Merdeka Curriculum in primary education.   Abstrak Rendahnya keterlibatan aktif peserta didik dan belum optimalnya keterampilan berpikir kritis dalam pembelajaran IPAS menjadi dasar pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis eksperimen pada materi sistem pernapasan manusia. Penelitian ini bertujuan menghasilkan perangkat pembelajaran yang valid, praktis, dan efektif digunakan oleh peserta didik kelas V Sekolah Dasar. Proses pengembangan mengikuti model ADDIE yang dimodifikasi melalui tahapan analisis, desain, pengembangan, implementasi, dan evaluasi. Validasi produk dilakukan oleh ahli materi, ahli media, dan ahli bahasa. Implementasi melibatkan guru serta peserta didik untuk menilai kepraktisan dan efektivitas LKPD dalam pembelajaran. Hasil pengembangan menunjukkan bahwa LKPD memiliki kualitas isi yang relevan dengan tujuan pembelajaran, disajikan dalam bentuk visual yang menarik, serta menggunakan bahasa yang komunikatif. Evaluasi pelaksanaan pembelajaran mengindikasikan bahwa produk mampu mendorong aktivitas belajar yang lebih kontekstual dan partisipatif. Dukungan dari respons guru dan peserta didik menguatkan bahwa LKPD dapat memfasilitasi keterampilan berpikir kritis peserta didik melalui eksperimen yang terarah dan bermakna. Kelayakan dan kepraktisan yang terpenuhi menjadikan LKPD ini sebagai salah satu alternatif media pembelajaran yang sesuai dengan karakteristik Kurikulum Merdeka dalam pendidikan dasar. Kata Kunci: berpikir kritis; eksperimen; LKPD; sistem pernapasan